PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS 3 SD IT BAITUL HAMDI PADANG - Maika Sari, Nita; Safarudin, Rizal; Suprizen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is based on the main problem of whether the implementation of the Cooperative Learning Model by teachers can improve the learning outcomes of Islamic Religious Education (PAI) for third-grade students at SD IT Baitul Hamdi Padang. The purpose of this research is to determine the level of student learning success through the application of the Cooperative Learning Model in PAI lessons to improve student learning outcomes. In addition, this research is expected to serve as a reference for applying various cooperative learning strategies and as a basis for developing cooperative learning models that actively engage students. This research employed Classroom Action Research consisting of four stages: preparation and planning, implementation of actions (pre-cycle, Cycle I, and Cycle II), and reflection. The results show that during the pre-cycle stage, students’ learning outcomes were relatively low, with a classical mastery level of 33% and an average score of 59.46. In Cycle I, classical mastery increased to 54% with an average score of 68.21. In Cycle II, a significant improvement was observed, with classical mastery reaching 87.5% and an average score of 85. A total of 21 students achieved scores above 70, while only 3 students scored below 70. Based on these findings, it can be concluded that the Cooperative Learning Model effectively improves PAI learning outcomes for third-grade students at SD IT Baitul Hamdi Padang.